Copper Nanoclusters: Cu14 Cluster with Partial Cu(0) Character: Difference in Electronic Structure from Isostructural Silver Analog (Adv. Sci. 18/2019). Issue 18 (18th September 2019) - Li, Yan‐Ling; Wang, Jie; Luo, Peng; Ma, Xiao‐Hong; Dong, Xi‐Yan; Wang, Zhao‐Yang; Du, Chen‐Xia; Zang, Shuang‐Quan; Mak, Thomas C. W.
Abstract : In article number1900833, Zhao‐Yang Wang, Shuang‐Quan Zang, and co‐workers present a simultaneous reduction strategy to synthesize an atom‐precise Cu 0 ‐containing cluster Cu14 ‐8CH3 CN with carborane dithiolate as the reducing‐cum‐protecting agent. Density functional theory calculations show that its electronic structure differs significantly from the superatom electronic configuration of the isostructural Ag14 analog. Moreover, Cu14 ‐8CH3 CN shows room‐temperature luminescence and good electrocatalytic activities in the ethanol oxidation reaction and detection of H2 O2 .